Co-productive agility and four collaborative pathways to sustainability transformations. (January 2022) - Chambers, Josephine M.; Wyborn, Carina; Klenk, Nicole L.; Ryan, Melanie; Serban, Anca; Bennett, Nathan J.; Brennan, Ruth; Charli-Joseph, Lakshmi; Fernández-Giménez, María E.; Galvin, Kathleen A.; Goldstein, Bruce E.; Haller, Tobias; et al.
Graphical abstract: Highlights: Explores how co-production processes can enable sustainability transformations. Four archetypes can hinder transformation: hero, host, woodpecker, genie. Co-productive agility opens up multiple pathways to transformation. Introduces a framework to enable agility in sustainability transformations. Challenges the tendency to close down rather than open up agendas for change. Abstract: Co-production, the collaborative weaving of research and practice by diverse societal actors, is argued to play an important role in sustainability transformations. Yet, there is still poor understanding of how to navigate the tensions that emerge in these processes. Through analyzing 32 initiatives worldwide that co-produced knowledge and action to foster sustainable social-ecological relations, we conceptualize 'co-productive agility' as an emergent feature vital for turning tensions into transformations. Co-productive agility refers to the willingness and ability of diverse actors to iteratively engage in reflexive dialogues to grow shared ideas and actions that would not have been possible from the outset. It relies on embedding knowledge production within processes of change to constantly recognize, reposition, and navigate tensions and opportunities. Co-productive agility opens up multiple pathways to transformation through: (1) elevating marginalized agendas in ways that maintain their integrity and broaden struggles for justice; (2) questioning dominant agendas by engaging with power in ways that challenge assumptions, (3) navigating conflicting agendas to actively transform interlinked paradigms, practices, and structures; (4) exploring diverse agendas to foster learning and mutual respect for a plurality of perspectives. We explore six process considerations that vary by these four pathways and provide a framework to enable agility in sustainability transformations. We argue that research and practice spend too much time closing down debate over different agendas for change – thereby avoiding, suppressing, or polarizing tensions, and call for more efforts to facilitate better interactions among different agendas.